Development of Research-Based Teaching Materials to Improve Critical Thinking Skills in the Use of Extremely Low Frequency Electromagnetic Waves to Increase Food Security - Agviolita, Putri; Sudarti, Sudarti; Narulita, Erlia (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
Critical thinking skills are needed in the 21st century, so efforts are being made to improve them, one of which is by developing research-based teaching materials, and research into the use of Extremely Low Frequency Electromagnetic waves to increase food security is currently being carried out very intensively. This research aims to describe the development of research-based teaching materials to improve critical thinking skills in the use of Extremely Low Frequency Electromagnetic waves to increase food security. This development research uses the Borg and Gall method, which consists of 10 steps. The subjects of this research were 90 students at the University of Jember. Undergraduate Physics Education students in classes A, B, and C in environmental physics courses and on material on the use of Extremely Low Frequency electromagnetic waves to increase food security. This research uses quantitative analysis. The results of this research state that research-based teaching materials are effective in improving students' critical thinking skills in the material on the use of Extremely Low Frequency Electromagnetic waves to increase food security with a score of 82.33 based on critical thinking indicators.